Post-traumatic severe ankle valgus and forefoot supination deformities treated by staged surgery using ilizarov technique and limited osteotomy: A case report. Issue 51 (23rd December 2021) - Zhang, Jie; Li, Yongmei; Liu, Luping; Chen, Leijie; Liu, Zhou; Duan, Qihui; Pu, Bo
Abstract: Rationale: Post-traumatic ankle valgus deformities are relatively rare. Old post-traumatic ankle deformity compounded by abundant scar contracture tissue formation around the joint is a big challenge for orthopedics. Conventional one-stage corrective osteotomy with internal fixation always results in many knotty postoperative complications, such as soft tissue avascular necrosis, implant-related infections, and distinct lower limb discrepancy. Here, we describe a patient with old post-traumatic severe ankle valgus and forefoot supination deformities and obtained satisfactory clinical results following multi-stage surgery using the Ilizarov technique and limited osteotomy. Even more encouraging, any complications of conventional one-stage surgery were successfully avoided through our treatment regimen. Patient concerns: A 24-year-old healthy man had post-traumatic 90-degree hindfoot valgus and forefoot supination deformities of the right foot for more than 10 years. The complicated issue was the vast, poorly vascularized scar contracture tissues tightly adhered to the bones of the lateral malleolus and dorsum pedis. Diagnoses: Old post-traumatic severe ankle valgus and forefoot supination deformities and scar contracture of soft tissues of the foot and ankle joint. Interventions: In the first stage, Ilizarov external fixation was used to stretch the scar contracture tissue of the lateral malleolus. In the second stage, limited osteotomy of the tibiotalar joint and progressive closure of the osteotomy site were performed. In the third stage, Chopart joint osteotomy and slow forefoot pronation by external frame were performed. Outcomes: Our treatment regimen not only guaranteed soft tissue safety, but also avoided infection and obvious lower limb discrepancy. At the 1-year follow-up, the patient acquired aesthetic and functional right foot. Lessons: Although relatively rare, old post-traumatic severe ankle valgus and forefoot supination deformities can be corrected using Ilizarov external fixation technology combined with limited osteotomy. With a well-designed staged operation scheme, soft tissue avascular necrosis, infection of the wound, obvious lower limb discrepancy, and flap grafting can be avoided.